Pengembangan Modul Interaktif Sebagai Sumber Belajar Ilmu Pengetahuan Alam Kelas V Materi Sistem Pernapasan Manusia - Eodhea Edwards Prabowo (Jurnal Pendidikan dan Konseling (JPDK), 2022)
Development of interactive learning modules using the type of R&D research. With the ASSURE development model which includes 6 stages, namely Learner Analysis, State Objectives, Select Media & Materials, Utilize Media & Materials, Require Learner Participation, Evaluation & Revision. The data analysis technique used in this study was descriptive and quantitative analysis, with the acquisition of the material validation test a score of 28 was obtained with a percentage of 56% in the fairly good category, while for media validation a score of 60 was obtained with a percentage of 80% in the good category. With the final results of the T test analysis with the calculated t value is -10.157 with sig. (2-tailed) 0.000 and sig 0.978 and df of 28. Probability value <0.05 then H0 is rejected and Ha is accepted, it can also be said that posttest academic results are higher than pretest. Based on this data, interactive learning modules are effective in an effort to improve student learning outcomes.